Borehole temperature measurements and drilling data at MeBo200 drill sites in the Black Sea and the South China Sea - Tim Freudenthal (PANGAEA, 2022)
Drilling data and borehole temperature data for one MARUM-MeBo200 drill site in the Black Sea (GeoB22605-1) and three MARUM-MeBo200 drill sites in the South China Sea (GeoB23213-1, GeoB23231-1, GeoB23234-1). Drilling data contain time, drilling depth and flush water flow rate, that is assumed to have an impact on the temperature distribution within the borehole. Borehole temperature data were measured at the end of the drilling operation with an autonomous borehole logging tool during trip out of the drill string. The temperature data sets contain time, depth of temperature sensor, and event descriptions that refer to the end of flush water operation as well as to the operation of the logging tool.